EXTH-76. 1H AND HYPERPOLARIZED 13C MRS BIOMARKERS OF IDH1 MUTANT GLIOMA RESPONSE TO TEMOZOLOMIDE THERAPY. (5th November 2018) - Subramani, Elavarasan; Najac, Chloe; Batsios, Georgios; Viswanath, Pavithra; Radoul, Marina; Gillespie, Anne Marie; Pieper, Russell; Ronen, Sabrina
Abstract: The alkylating agent temozolomide (TMZ), previously reserved for treatment of glioblastoma, is now being considered for the treatment of low-grade glioma that are driven by mutations in the isocitrate dehydrogenase 1 (IDH1) gene. Though the treatment of IDH1 mutant patients with TMZ improves survival, there is a need for metabolic imaging to help in assessing early response to therapy. The goal of this study was, therefore, to determine the value of magnetic resonance spectroscopy (MRS)-based biomarkers for detection of response to treatment. To address this, we examined the global metabolic alterations that occurred following TMZ treatment in a genetically engineered IDH1 mutant immortalized normal human astrocyte cell line (NHAIDHmut) using 1 H and 13 C MRS combined with chemometrics. Cells were treated either with the IC50 of TMZ (100 μM; N=5), or with DMSO (0.2%; N=5) for 72 hours. Then, metabolites were extracted from cells and 1 H spectra acquired. Data were analyzed using SIMCA and the most significant metabolites contributing to class separation were identified using multivariate and univariate analyses. Alternatively, live cells were exposed to hyperpolarized 2- 13 C-pyruvate and dynamic sets of 13 C-MRS spectra recorded to monitor the production of 5- 13 C-glutamate over time. 1 H MRS showed that glutamine, glutamate, pyruvate, succinate, glucose, phosphocholine, isoleucine, valine, lysine, phenylalanine, NAD+/NADP+ and ATP/ADP/AMP were significantly higher in TMZ-treated cells as compared to controls. Accordingly, the tricarboxylic acid (TCA) cycle was identified as a significantly altered pathway following TMZ treatment. Consistent with this finding, dynamically probing the metabolism of hyperpolarized 2- 13 C-pyruvate revealed that build-up of 5- 13 C-glutamate, which is associated with flux to the TCA cycle, was significantly higher in TMZ-treated cells as compared to controls. Further studies are warranted for validation of our findings in other mutant IDH1 models. Nonetheless, our findings identify potential MRS-detectable early biomarkers of response to TMZ therapy in mutant IDH1 glioma.